A Rare Fracture of The Mandible - Sulabha, AN; Sameer, AC; Warad, NM (Bangladesh Journal of Medical Science, 2012)
Maxillofacial traumas are common and mandible is most frequently fractured bone in the lower third of face. Here we report a rare horizontal fracture of mandible from right molar to left molar. Fracture was adequately reduced and fixed with two holed miniplates. The possible mechanism of such an unusual fracture is discussed. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12611 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12